Pengaruh Penggunaan E-Book Ensiklopedia Tata Surya dengan Pendekatan TPACK Terhadap Hasil Belajar dan Minat Belajar pada Pembelajaran IPA Siswa Kelas VI - Desy Putri Sari; Irwan Koto; Osa Juarsa (Jurnal Kajian Pendidikan Dasar, 2024)
This study aims to determine the effect of using the solar system encyclopedia e-book with the TPACK approach to learning outcomes and learning interest in science learning for class VI students. This research is a quantitative research, with a Quasi Experimental Design approach. The population in this study were all grade VI students at SD N 14 Lubuklinggau. The sample in this study were 27 students of class VI.A as the experimental class and 26 students of class VI.B as the control class. The instruments used in this study were interview guides, questionnaires, and pretest and posttest tests. Based on the calculation results obtained 7.796 > 2.010 or it can be concluded t-count > t-table. The result of the significance value analysis is 0.000, which means it is less than 0.05, so it can be concluded that Ho is rejected. Thus, there are significant differences in learning outcomes in solar system material whose learning process uses encyclopedia e-books. Also, Cohen's result d = 2.136 (large effect size). The effect size we mean is the difference between the mean values ​​of the two groups in relation to the standard deviation which shows the results of the effect size with the high category. Testing the hypothesis stated that there was an interest in learning for class VI students about the solar system by using an e-book encyclopedia. The calculation results obtained 1.840 > 2.010 or it can be concluded that t-count > t-table. The significance value of the analysis results is 0.000, which means it is less than 0.05. Cohen result d = 2.023 (large effect size) By effect size, we mean the gap between the mean values ​​of the two groups in relation to the standard deviation indicating an effect size result in the high category. This study shows that there is a significant effect of encyclopedia e-books with the TPACK approach on the results and interest in learning science in grade VI students.